Increased risk for metachronous gastric adenocarcinoma following gastric MALT lymphoma—A US population-based study. Issue 4 (June 2017) - Palmela, Carolina; Fonseca, Cristina; Faria, Rita; Baptista, Rute Baeta; Ribeiro, Sofia; Ferreira, Alexandre Oliveira
Background: Gastric mucosa-associated lymphoid tissue lymphoma (gMALT) and gastric adenocarcinoma (GC) are long-term complications of chronic Helicobacter pylori (HP) gastritis. Treatment of HP infection induces remission in most patients with gMALT. Endoscopic follow-up is not currently endorsed after complete remission. However, the risk of GC in these patients is unclear. Objective: The objective of this study is to estimate GC risk in gMALT patients. Methods: The National Cancer Institute Surveillance, Epidemiology and End Results 13 (SEER) database-Nov 2014 Sub (1992–2012) was used to identify adult patients diagnosed with gMALT between 1992 and 2012. The standardized incidence ratio of second primary GC after a latency period of 12 months was calculated and compared to a reference SEER cohort of identical age, sex and time period. The risk of GC in these patients was also stratified by latency period (five years) and age. Results: We identified 2195 cases of gMALT lymphoma, and 20 (0.91%) of them subsequently developed GC with a relative risk (RR) of 4.32 (95% CI 2.64–6.67) compared to the American population. The median latency time was five years and the risk was maintained afterward (RR 4.92, 95% CI 2.45–8.79). When stratified by age group the risk was highest for the 45–64 group (RR 14.04, 95% CI 5.64–28.93). Conclusion: gMALT lymphoma is associated with an increased risk of metachronous gastric adenocarcinoma. The risk is still present after more than five years of follow-up. Further studies may clarify the most adequate follow-up strategy.